2017
DOI: 10.3390/molecules22101791
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Disrupts Subcellular Organelles, Including Chloroplasts, Resulting in Melatonin Induction in Plants

Abstract: Cadmium is a well-known elicitor of melatonin synthesis in plants, including rice. However, the mechanisms by which cadmium induces melatonin induction remain elusive. To investigate whether cadmium influences physical integrities in subcellular organelles, we treated tobacco leaves with either CdCl2 or AlCl3 and monitored the structures of subcellular organelles—such as chloroplasts, mitochondria, and the endoplasmic reticulum (ER)—using confocal microscopic analysis. Unlike AlCl3 treatment, CdCl2 (0.5 mM) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…This would be a very fortuitous arrangement given the fact that, as already mentioned herein, mitochondria have a propensity to produce an abundance of free radicals as a byproduct of oxidative phosphorylation [ 57 , 71 , 142 , 157 ]. Recently published data supports the high likelihood that both mitochondria [ 71 , 100 , 101 , 102 , 160 ] and chloroplasts [ 161 , 162 ] are in fact sites of melatonin synthesis.…”
Section: Melatonin In Mitochondria: a Fortuitous Associationmentioning
confidence: 83%
“…This would be a very fortuitous arrangement given the fact that, as already mentioned herein, mitochondria have a propensity to produce an abundance of free radicals as a byproduct of oxidative phosphorylation [ 57 , 71 , 142 , 157 ]. Recently published data supports the high likelihood that both mitochondria [ 71 , 100 , 101 , 102 , 160 ] and chloroplasts [ 161 , 162 ] are in fact sites of melatonin synthesis.…”
Section: Melatonin In Mitochondria: a Fortuitous Associationmentioning
confidence: 83%
“…It was found that Al significantly increased melatonin content in soybean . In other plants, however, it has been reported that melatonin levels decreased, for example, in the roots of Arabidopsis after Al treatment, but not changed in rice seedlings . Most of studies have only employed a single genotype with undefined resistance to Al stress.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed the important roles of melatonin in regulating plant growth, development, and responses to the various environmental stresses [ 14 , 15 ]. Melatonin acts as bio-stimulator in plants by enhancing the tolerance against abiotic stresses [ 16 , 17 ], including high temperature [ 18 , 19 , 20 ], cold and chilling [ 21 , 22 , 23 , 24 , 25 ], drought [ 26 ], salt [ 27 , 28 , 29 ], heavy metal [ 30 , 31 , 32 , 33 , 34 ], acid rain [ 35 ], and biotic stresses such as pathogen attacks [ 12 ]. Similar to the other abiotic stresses, cadmium pollution was a major environmental concern for its toxic actions to plants and animals [ 36 ].…”
Section: Introductionmentioning
confidence: 99%